All Days 1992
DOI: 10.4043/6965-ms
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Lightweight Moorings for Deep Water

Abstract: This paper outlines the potential advantages of using lightweight fiber ropes for mooring floating production platforms. The influence of tether properties on mooring system response is discussed. It is shown that a comparison of alternative ropes in terms of their mechanical properties is inadequate; relative merit can only be assessed through comparison of full systems that have been designed to minimum cost, and to common performance specifications. For catenary systems, it is found that a lightweight optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…As highlighted by Chaplin and Del Vecchio (1992), system design is strongly influenced by the non-linear visco-elastic behavior of polyester ropes. Therefore obtaining tether properties at all relevant loading regimes, to use in design, is essential.…”
Section: Design Procedures and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted by Chaplin and Del Vecchio (1992), system design is strongly influenced by the non-linear visco-elastic behavior of polyester ropes. Therefore obtaining tether properties at all relevant loading regimes, to use in design, is essential.…”
Section: Design Procedures and Parametersmentioning
confidence: 99%
“…Results of a comprehensive study on the use of fiber ropes for deepwater moorings were presented in 1992 (Chaplin & Del Vecchio, 1992). Full details of the study, including assessment of failure modes, load-elongation behavior, design methodologies and criteria were produced .…”
Section: Introductionmentioning
confidence: 99%
“…Recently polyester was used in field trials down to 1900 meters depth 5 but there are few guidelines concerning alternative materials. Chaplin & Del Vecchio compared polyester ropes to steel at depths of 500, 1000 and 2000 meters 6 . Cloos & Bosman compared nylon, polyester, and aramid ropes at depths to 3000 meters and concluded that there is a minimum depth for each material, that for aramid being 1000 meters 7 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As with many other proposed new drilling technologies, actual field experience specific to MODUs is limited. The use of synthetic fiber lines can greatly reduce the vertical loads on the rig, enable the use of existing winches in greater water depths, and/or increase the amount of available variable deck load.…”
Section: Introductionmentioning
confidence: 99%